Kha-Yot Model: Innovative Participatory Waste Management, Bung Wang Ngio Community, Uttaradit Province - Phromnoi, Siriwadee; Phanthong, Watsana; Sampoosree, Soiratda; Insueb, Sueb (Area Based Development Research Journal, 2020)
The study on the ‘Kha-Yot Model’ aims to develop an innovative participatory waste management in the Bung Wang Ngio community, Pa-Sao sub-district, Muang district, Uttaradit province. ‘Kha-Yot Model’ refers to the process of applying science and technology knowledge for waste management mechanism in the community, conducted in 2016-2018. The concept of 3Rs was adapted for waste reduction, technology-based value-added waste management, and life quality improvement for the community. This participatory research enabled networking among the various organizations including Pa-Sao subdistrict municipality, Bung Wang Ngio community, and Uttaradit Rajabhat University. In 2018, under the innovation in waste management the "Kha-Yot Model”, the amount of waste products in the community decreased by 23.53% to 1.04 kilograms per person per day, which is lower than the national average incidence rate of waste products in Thailand. The recyclable waste reduced from 50.91% to 37.52% and organic waste reduced from 45.15% to 43.06%. In addition, relevant management mechanisms were initiated such as community waste banks, Environmental Fund for the Elderly, and Community Waste Management Learning Center. Overall, households participating in the waste management process increased from 178 households to 356 households or every household in the community. Consequently, the Ban Bung Wang Ngio community, as the pilot project area has developed a trash-free village and is able to manage waste products independently and sustainably.